Post-fire compressive behaviour of carbon fibers woven-ply Polyphenylene Sulfide laminates for aeronautical applications. (15th June 2017) - Maaroufi, M.A.; Carpier, Y.; Vieille, B.; Gilles, L.; Coppalle, A.; Barbe, F.
Abstract: The influence of fire exposure on the residual compressive behaviors of carbon fibers woven-ply Polyphenylene Sulfide has been investigated for aeronautical applications. For heat fluxes ranging from 20 to 50 kW/m 2, prior fire exposure is highly detrimental to the compressive mechanical properties as the residual strength and stiffness decrease by −75% and −55% respectively. Thermogravimetric analyses have been conducted under inert and oxidative atmospheres to quantify the mass loss resulting from the thermal decomposition of the outer layer directly exposed to heat flux and oxygen-rich atmosphere and internal layers respectively. Fire exposure results in gradually increasing damages within exposed laminates: PPS matrix thermal decomposition leaves intra- and inter-laminar voids leading to more or less extensive delamination depending on fire testing conditions. In order to discuss the compressive damage mechanisms after fire, the early deformation mechanisms have been analyzed by means of 2D Digital Image Correlation. C-scan inspections have also been performed to evaluate the delaminated areas which are quite well correlated with the surface fire-degraded areas, suggesting that delamination is primarily associated with thermal degradation. As heat flux increases, the fire-induced delamination and the onset of local plastic kink-bands during compressive loading ultimately cause delamination extension and global plastic buckling.